Endovascular Access to the Meningohypophyseal Trunk - Borden, Neil M.; Liebman, Kenneth M. (American Journal of Neuroradiology, 2001)
Summary: We describe a novel technique to selectively catheterize the meningohypophyseal trunk (MHT) and its branches. We emphasize the difficulty in accessing the MHT via an ipsilateral approach because of the geometric orientation of this vessel to the parent internal carotid artery.